Hip Fracture Overview: Integrating Medical, Nutritional, Rehabilitation, and Psychological Care - Alzaidi, Nada Abdulaziz Faraj; Moatsem Eid Saleh ALsenani; Luay Mohammed Abdu Faqihi; Hussain Mohammed Hussain Alwabari; Muath Sami Alawad; Eman Abdulmohsen Alsaleh; Dabiaha Shabnan Saed Alshahrani; Khaled Mohammed Mousa Swid; Wejdan Mohammed Althurwi; Ammar Ali Hakami (Saudi Journal of Medicine and Public Health, 2025)
<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Background:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Hip fracture is a major global health concern, particularly among the elderly, associated with high morbidity, mortality, and economic burden. It typically results from low-energy falls in osteoporotic individuals, though high-energy trauma causes fractures in younger patients. Effective management requires a comprehensive, integrated approach addressing far more than the fracture itself. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Aim:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> This review provides a holistic overview of hip fracture care, integrating medical, surgical, nutritional, rehabilitation, and psychological perspectives to optimize patient outcomes from emergency presentation through to long-term recovery and secondary prevention. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Methods:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> A narrative synthesis of current evidence and clinical guidelines is presented, covering epidemiology, classification, multidisciplinary evaluation, surgical management options, and the critical roles of perioperative optimization and structured rehabilitation. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Results:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Diagnosis relies on clinical assessment and imaging, with MRI for suspected occult fractures. Treatment is predominantly surgical, with the approach dictated by fracture type and patient factors: arthroplasty (total hip or hemiarthroplasty) for displaced intracapsular fractures in the elderly, and internal fixation for undisplaced intracapsular and most extracapsular fractures. Outcomes are significantly improved by early surgery (within 48 hours), effective pain control (e.g., nerve blocks), and a coordinated orthogeriatric model of care. This multidisciplinary approach addresses medical comorbidities, delirium prevention, nutrition, and early mobilization, which are essential to mitigate complications like thromboembolism, infection, and functional decline. <span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-weight: bold; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;">Conclusion:<span style="font-size: 11pt; font-family: Aptos; background-color: transparent; font-variant-numeric: normal; font-variant-east-asian: normal; font-variant-alternates: normal; font-variant-position: normal; font-variant-emoji: normal; vertical-align: baseline; white-space-collapse: preserve;"> Successful hip fracture management necessitates an interprofessional, patient-centered strategy. Combining timely, evidence-based surgery with comprehensive medical, nutritional, and rehabilitative support improves survival, functional recovery, and quality of life while emphasizing the importance of falls prevention and osteoporosis treatment for secondary prevention.